2019
DOI: 10.1016/j.clinbiomech.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of acetabular press-fit cups: Influence of design and surgical factors

Abstract: Background: Deformation of acetabular cups when press-fitted into an undersized cavity is inevitable due to the inhomogeneous stiffness of acetabular bone. Thinner cups or screw holes might increase the risk of high cup deformation. The aim of this study was to examine the influence of cup design and liner assembly on the deformation response during cup implantation. Methods: Acetabular cups with different designs were implanted into polyurethane foam models simulating the anatomical situation with nominal pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…This coincides with the higher deflections due to the lower cup stiffness of the thin-walled cups 19,33 and results in lower contact stresses to the bone. The previously demonstrated correlation of cup deflection and lever out moment 18 was in the present study only demonstrated for the thick-walled design. The thin-walled cups were found to be more robust exhibiting a rather constant high primary stability.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This coincides with the higher deflections due to the lower cup stiffness of the thin-walled cups 19,33 and results in lower contact stresses to the bone. The previously demonstrated correlation of cup deflection and lever out moment 18 was in the present study only demonstrated for the thick-walled design. The thin-walled cups were found to be more robust exhibiting a rather constant high primary stability.…”
Section: Discussioncontrasting
confidence: 64%
“…The insertion of hard liners can lead to a significant reduction in deformation. 18 High cup deformations do not necessarily lead to improper liner seating or excessive liner deformation but certainly, make the liner insertion more difficult. A detailed analysis of the time-dependent cup deformation could also help to assess whether liner insertion may benefit from a specific relaxation time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-hole cups have been shown to present more deformation than single-hole cups during implantation [16], which allows one to assume that a similar effect may be seen under dynamic loading after implantation. For the purpose of comparability, a multi-hole cup was used in both scenarios, although this type of cup would tend not to be used clinically in a scenario without a bony defect.…”
Section: Limitationsmentioning
confidence: 99%
“…Prior studies have focused on assessing the pattern and degree of deformation resulting from the implantation process [7,[9][10][11][12][13][14]. A few studies have assessed deformation after press-fit implantation and load application [15,16], however, these studies did not investigate cup deformation during load on the cup, as would be the case once the patient moves his/her hip.…”
Section: Introductionmentioning
confidence: 99%